A mesoporous SiO2/TiO2 composite used for various emulsions separation. Issue 6 (13th April 2019) - Ge, Bo; Han, Lu; Gao, Bo; Zhang, Tingxiao; Li, Xiuling; Zhu, Xiaotao; Pu, Xipeng; Li, Wenzhi
ABSTRACT: A mesoporous SiO2 -TiO2 - x composite without any modification was obtained to separate oil-in-water and water-in-oil emulsions solely by gravity. To simulate the actual pollution treatment process in sewage treatment plants, adsorption and degradation properties were studied after the initial emulsion separation. The research result indicates that the reported mesoporous SiO2 can be employed as an excellent absorbent and catalyst carrier. After light irradiating for 120 min, the degradation efficiency of SiO2 -TiO2 -4 for Rhodamine B, methyl orange, methylene blue, and ciprofloxacin hydrochloride reaches 99.3%, 91.5%, 98.7%, and 96.2%, respectively.